Effects of bottom roughness on wave transmission across a submerged reef - Dinh, Quang Cuong; Nguyen, Quang Tao; Ho, Duc Dat; Mai, Cao Tri (Frontiers in Marine Science, 2023)
This paper presents a laboratory study to investigate the effects of bottom roughness on wave transmiting across a submerged coral reef having a steep fore-reef slope. Experimented models were carried out in wave flume for four different bed roughness levels including a smooth and three roughness heights. Investigations showed that there is a significant dissipation in energy of short-period waves (SS-waves) due to bottom friction compared to that of infra-gravity waves (IG-waves). In addition, it is found that the IG-wave heights are slightly increased as waves propagate shoreward from the reef-edge surfzone, indicating a significant portion of energy have been transferred from SS-waves to IG-waves. Empirical formulas of wave energy dissipation due to bottom friction and non-linear transference of energy amongst the SS- and IG-waves have been derived, which allow for straightforward determining wave heights and wave periods on the submerged reef. These local wave parameters can be used to design offshore structures on submerged coral reefs.